2016
DOI: 10.3233/jad-160953
|View full text |Cite
|
Sign up to set email alerts
|

Localization and Processing of the Amyloid-β Protein Precursor in Mitochondria-Associated Membranes

Abstract: Alteration of mitochondria-associated membranes (MAMs) has been proposed to contribute to the pathogenesis of Alzheimer’s disease (AD). We studied herein the subcellular distribution, the processing, and the protein interactome of the amyloid-β protein precursor (AβPP) and its proteolytic products in MAMs. We reveal that AβPP and its catabolites are present in MAMs in cellular models overexpressing wild type AβPP or AβPP harboring the double Swedish or London familial AD mutations, and in brains of transgenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
118
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(133 citation statements)
references
References 86 publications
6
118
0
4
Order By: Relevance
“…Additionally, the KPI domain of APP, which is predominantly expressed in astrocytes, has been shown to be important for APP localization to mitochondrial (Wang et al, ). More specifically, APP localizes at the translocase of the outer mitochondrial membrane (TOMM) complex, where it affects the import of nuclear encoded proteins into mitochondria (Del Prete et al, ). Intriguingly, this mechanism appears disrupted in AD and APP tends to accumulate around TOMM complexes under pathophysiological conditions (Anandatheerthavarada, Biswas, Robin, & Avadhani, ; Del Prete et al, ; Devi, Prabhu, Galati, Avadhani, & Anandatheerthavarada, ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the KPI domain of APP, which is predominantly expressed in astrocytes, has been shown to be important for APP localization to mitochondrial (Wang et al, ). More specifically, APP localizes at the translocase of the outer mitochondrial membrane (TOMM) complex, where it affects the import of nuclear encoded proteins into mitochondria (Del Prete et al, ). Intriguingly, this mechanism appears disrupted in AD and APP tends to accumulate around TOMM complexes under pathophysiological conditions (Anandatheerthavarada, Biswas, Robin, & Avadhani, ; Del Prete et al, ; Devi, Prabhu, Galati, Avadhani, & Anandatheerthavarada, ).…”
Section: Introductionmentioning
confidence: 99%
“…These regions constitute an almost direct pathway for Ca 2+ transfer from the ER to mitochondria, thanks to the presence of IP 3 R in the ER, voltage-dependent anion channels in the outer mitochondrial membrane, and mitochondrial Ca 2+ uniporters in the inner mitochondrial membrane, together with many other proteins that form long-lasting structures that keep ER and mitochondrial membranes at distances of 10-30 nm. It has been shown that presenilins and APP are ER integral membrane proteins that are enriched in the MAMs [56][57][58], so they can easily interact with all the machinery for ER-mitochondria Ca 2+ transfer. In fact, several Alzheimer's disease inducers or presenilin mutations enhance ER to mitochondria Ca 2+ transfer through these structures [59].…”
Section: Dysregulation Of Ca 2+ Signaling In Aging and Neurodegenerationmentioning
confidence: 99%
“…Interestingly, the proteolytic activity of PreP is decreased in the AD brain [31]. Aβ can be localized to the inner mitochondrial membrane [32], and constituents of the γ-secretase complex, such as nicastrin, APH-1, PEN-2, and presenilin-1, which function in APP processing, are also localized within the mitochondria-associated membrane [33,34]. It has been reported that mitochondrial dysfunction and neurodegeneration occur in model mice with deleted HtrA2, a serine protease that interacts with Aβ, APP, and presenilin-1 within the intermembrane space [35].…”
Section: Interaction Of Amyloid and Neuronal Mitochondriamentioning
confidence: 99%